1991
DOI: 10.1073/pnas.88.20.9335
|View full text |Cite
|
Sign up to set email alerts
|

The phenotype of lymphoid cells and thymic epithelium correlates with development of autoimmune insulitis in NOD in equilibrium with C57BL/6 allophenic chimeras.

Abstract: The mechanisms contributing to the development of autoimmune insulin-dependent diabetes mellitus have been analyzed in allophenic mouse chimeras of the NOD +* C57BL/6 strain combination (where NOD is nonobese diabetic). Occurrence of lymphoid cell infiltration (insulitis) in pancreatic islets was observed in the majority of such chimeras. The development of insulitis was found to correlate with major histocompatibility complex chimerism in lymphoid cells and in thymus cortical regions. Chimeras with more than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Hence, NOD-allophenic mice can be used to dissect the cellular mechanisms involved in the pathogenesis of the autoimmune process. For example, we found previously that the ailophenic chimeras lacking the NOD component in thymic epithelium consistently failed to develop insulitis [24], supporting the notion that thymic positive selection of T cells is essential for development of this spontaneous, tissue-specific autoimmunity. In that experiment, however, although many NOD*-vC57BL/6 ailophenic mice showed insulitis and extensive destruction of l^ cells in the islets, none of them developed diabetes.…”
Section: Introductionsupporting
confidence: 65%
“…Hence, NOD-allophenic mice can be used to dissect the cellular mechanisms involved in the pathogenesis of the autoimmune process. For example, we found previously that the ailophenic chimeras lacking the NOD component in thymic epithelium consistently failed to develop insulitis [24], supporting the notion that thymic positive selection of T cells is essential for development of this spontaneous, tissue-specific autoimmunity. In that experiment, however, although many NOD*-vC57BL/6 ailophenic mice showed insulitis and extensive destruction of l^ cells in the islets, none of them developed diabetes.…”
Section: Introductionsupporting
confidence: 65%
“…We had previously observed that the proportion of NOD lymphocytes in EA chimeras correlated with the development of insulitis [ 15] and with subsequent CY‐induced diabetes [ 16]. In order to assess whether the lymphoid chimerism would also affect diabetes susceptibility in the transfer model, the chimerism was measured in the donor spleen cells at the moment of transfer, and in the spleens of the recipients at death.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of graft‐versus‐host disease can therefore be excluded. NOD <−> B6 EA chimeras develop spontaneous autoimmune insulitis but are virtually resistant to IDDM [ 15]. Similar to diabetes‐free NOD male mice, the resistance in EA chimeras can be overriden by cyclophosphamide (CY) treatment [ 16].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed below, if the Yaa gene effect can be associated with the recognition by T helper cells of the putative Yaa-related antigen expressed on B cells, the I-A molecule may be involved in the selection or deletion of T cells with anti-Yaa specificity or in the presentation of the Yaa antigen-derived peptides. In this regard, a recent elegant study of Forsgren et al [13] is relevant. Finally, it should be emphasized that the MHC gene is not the only autosomal gene to be involved in the action of the Yaa gene, since the autoimmune accelerating activity of the Yaa gene is observed in BXSB (H-2 b) and MRL (H-2 k) mice, but not in non-autoimmune mice bearing the same H-2 haplotype, B6 (H-2 b) and CBA/J (H-2 k) [23,31].…”
Section: Role Of the Major Histocompatibility Complex Genes In The Yamentioning
confidence: 99%